Disseminated cysticercosis with a right common femoral vein thrombosis - Singh, Utpal Kant (BMJ Publishing Group, 2013)
Disseminated cysticercosis is an uncommon presentation of cysticercosis. Less than 10 cases of disseminated cysticercosis have been reported worldwide in children. We report the case of an 8-year-old boy with disseminated cysticercosis, who had presented with a swelling of the body for 1 month and proptosis of the eyeballs for 14 days. On examination, he had bilateral proptosis, subcutaneous nodules and hypertrophy of muscles of the limbs, neck and face. The CT cranium was normal, but the orbit showed bilateral bulky extraocular muscles heterogeneous in their whole length. The MRI cranium and whole body showed multiple non-enhancing vesicular cysts involving the brain, extraocular muscle, heart, trunk and muscles of the extremities and subcutaneous tissues. A Doppler study of the femoral vein showed thrombosis of the right common femoral vein. He was managed with corticosteroid, albendazole, phenytoin sodium, low-molecular-weight heparin followed by warfarin for 6 months and recovered completely.